Tinjauan Pengendalian Kualitas Produk Menggunakan Metode Failure Mode And Effect Analysis di PT. XYZ - Sudjiand Arya Kresna; Ade Momon Subagyo (Peneliti.net, 2022)
This study was conducted with the aim of knowing the type of dominant defect that occurs in one of the Cover 655B products, knowing the factors that cause the product to occur in the product, and provide proposed improvements on how to improve the quality of Cover 655B products that currently still occur frequently in the span of three months, namely in November 2021 to January 2022. The problem approach contained in this study is to use the Pareto Diagram tool, as well as data processing and proposed improvements using the Failure Mode and Analysis (FMEA) method. Priority improvement based on the largest Risk Priority Number (RPN) value is in the engine parameter setting activity is not in accordance with the standard setting, and the mold cooling system does not work properly with an RPN value of 27, the proposed improvement is that the operator must often check the engine setting parameters with actual parameter setting conditions, and the operator must also ssering Check flow in-out cooling system, and check the part or mold in the production process